“Teaching Unplugged”: An Approach For Designing An EFL Teacher Education at Disadvantaged Schools - Febrianto, Aziza Restu; Pavita, Maria Dimitrij Angie; Normawati, Afi (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2024)
Inspired by the approach of “Teaching Unplugged: Dogme in English Language Teaching” developed by Luke Meddings and Scott Thornbury, this theoretical research introduces and offers a conceptual design of teacher training intended to be relevant to novice Indonesian EFL teachers, especially those working at schools located in the most remote and disadvantaged areas of Indonesia. The training is designed based on the theoretical framework of the approach and critical reviews of several related empirical studies. This article, therefore, focuses on exploring the applications of the approach by examining some other research including the most recent ones about the approach, and investigating its relevance to the context of English education at the most disadvantaged schools in Indonesia. The practical stages and syllabus are also presented in the article so that both teachers as participants and teacher educators can easily follow and understand how the materials can be implemented in their teaching contexts. Considering the theoretical-based materials and well-planned activities that the training offers, novice EFL teachers, after completing the program, are expected to be able to improve their both language and pedagogical skills that are needed in their school contexts and in line with the recent curriculum, the Merdeka curriculum.